Export of Russian Higher Education Services: Tools and Current Results - A. M. Pogorelskaya; L. V. Deriglazova (Moscow Polytechnic University, 2024)
The research aim is to analyze how the tools for promoting export of Russian higher education as a service have changed (if they have) and identify the results of their application.   The study is based on the analysis of Russian official and departmental documents regulating educational export, as well as statistical data on Russian higher education system. Literature analysis indicates growing research interest in educational export, but there is no common methodology for assessing its effectiveness. Using indicators elaborated by researchers and analysts, authors try to classify the specific instruments for higher education export and access their results at the country level and the National Research Tomsk State University (TSU). It is concluded that Russia uses three groups of tools to promote higher education export to generate income, attract talents and improve the living conditions of students. The effectiveness of these tools is relative due to external circumstances (COVID-2019 pandemic, the sanctions regime against Russia) and the higher education system itself, for which the interpretation of education as a service is relatively new. The case of TSU shows that provincial universities mainly educate students from the CIS countries, and they were able to relatively quickly reorient their activities. At the same time, Russia faces increased competition with other countries in the CIS, and the high cost of education export instruments (the creation of branches, joint educational programs) forces them to make additional efforts to recruit students even at traditional directions of education export.